New Advances for the Application of Eucalyptus as a Structural Wood - Santos,J. António (2004)
The authors of this paper intend to present the techniques being developed through laboratory experiments in the mechanical characterization of one species wood, namely eucalyptus (blue gum) aimed at new structural applications, using reconstructed glued components. Knowledge in this field dealing with wooden structures is innovative for fast grown Hardwoods. Bibliographic research revealed very little information on this subject and that which is available, is still based on empirical knowledge referring the possibilities and interest of glued components of this species. This presentation is considered relevant since this material is abundant in Portugal and has been introduced in many other countries, but primarily for the purpose of pulp production. In this work the first results of tests on eucalyptus wood will be presented, namely static bending tests of glued lamellas of eucalyptus and tests on small clear specimens. The values of the global modulus of elasticity in bending and the yield strength are presented for both glued specimens and for small solid, defect free specimens, in accordance with procedures defined in recent European standards for these types of structural components.